SURGICAL OUTCOME OF RECURRENT LUMBAR DISC HERNIATION: EXPERIENCE WITH 30 PATIENTS - Khattak, Azmat Ullah; Haider, Ali; Rehman, Lal; ., Ilyas; ., Mushtaq (Journal of Postgraduate Medical Institute, 2011)
Objective: To study the outcome of recurrent lumbar disc herniation managed surgically. Material and Methods: This retrospective study was conducted in Neurosurgery Department of Lady Reading Hospital and Hayatabad Medical Complex, Peshawar from Mar, 2005 to Feb, 2008 with 06 month follow-up. This study included patients who underwent re-do surgery for re-herniation of lumbar disc herniation at previous operated level of L4-5 and L5-S1. Data was collected on a proforma containing name, age and sex of patients along with findings of previous surgery, clinical outcome of previous surgery, present neurological status with signs and symptoms, investigations, complications and follow-up findings. Results: Thirty patients including 22 (73.33%) male and 08 (26.66%) female were operated upon for recurrent lumbar disc herniation. Twenty two (73.3%) patients were pain free after surgery. Improvement in SLR was 80% (n=24/30) complications after 01 month. Overall complication rate was 40%. Five (16.66%) patients had dural in which 02 (6.66%) postop CSF leak, 01 (3.33%) had superficial wound infection, 01 (3.33%) had discitis, 01 (3.33%) had foot drop and 02 (6.66%) had urinary retention. Patients with foot drop did not showed any improvement postoperatively after 06 month of follow-up. Conclusion: Surgery for recurrent lumbar disc herniation appears to be effective procedure in which better overall outcome and improvement in pain can be achieved.